Análise das competências e responsabilidades do testador ágil no contexto nacional - Inhaquite, Vanessa Américo Fernandes (Universidade do Vale do Rio dos Sinos, 2016)
Due to the need for more research on Agile Software Testing area and to understand what is the role of the tester and what are their competencies in an agile development environment, this study aims to analyze the main competencies and responsibilities of this role through a survey performed with testers in the national context. From the results obtained in this study it was possible to identify the more present and important competencies and responsibilities from the point of view of these testers, as well as an overview of the state of practice on the operation, competencies and responsibilities of this professional in agile development.
Keywords: Teste de software agil; Ambiente de desenvolvimento; Agile software testing; Development environment